Zinc oxide and gold textured Janus nanowire integration in an impedimetric sensor for leptospirosis DNA-biomarker recognition - Haarindraprasad, R. (John Wiley and Sons Inc, 2022)
A âJanus particleâ refers to the production of two materials in a single system and shows a difference in physical characteristics, and two surfaces participate in the formation with different chemistries. This research generated the Janus using a hybrid of zinc oxide (ZnO) and gold (Au) on the sensor surface toward making high-performance DNA sensors. The Janus ZnO/Au-textured film was synthesized via the one-step solâgel method, which involves a suitable ratio of a mixture of ZnO sol seed solution. The synthesized Janus ZnO/Au-textured film undergoes a low-temperature aqueous hydrothermal route to synthesize quasi-one-dimensional nanowires. The average grain size in the Janus ZnO/Au nanotextured wire was 41.60 nm. The fabricated nanotextured wire was further optimized by tuning the thickness and characterized by XRD and high-resolution microscopy. Electrical characterization was conducted on the Janus ZnO/Au nanotextured wire coupled with an interdigitated electrode sensor to detect the specific leptospirosis DNA strand. The generated device is capable of detecting lower DNA concentration at 1 Ã 10â13 M with a sensitivity of 8.54 MÎ© Mâ1 cmâ2. The high performance is attained on linear concentrations of 10â6â10â13 M with the determination coefficient, âI = 135437.63Câ3609.07â R2 = 0.9551. A potential strategy is proposed as a base for developing different high-performance sensors. Â© 2022 International Union of Biochemistry and Molecular Biology, Inc.